Coefficients estimates for functions inBn(α) - Abdul Halim, S. (Hindawi Publishing Corporation, 2003)
We consider functions f, analytic in the unit disc and of the normalised form f(z)=z+∑k=2∞akzk . For functions f∈Bn(α), the class of functions involving the Sălăgean differential operator, we give some coefficient estimates, namely, |a2|, |a3|, and |a4|.